Structural analysis of glycosaminoglycans from Oviductus ranae - Huang, Haiyue; Mao, Jin; Liang, Quntao; Lin, Jianghui; Jiang, Lilong; Liu, Shutao; Sharp, Joshua S.; Wei, Zheng (Glycoconjugate journal, 2021)
Oviductus ranae ( O.ran. ) has been widely used as a tonic and a traditional animal-based Chinese medicine. O.ran. extracts have been reported to have numerous biological activities, including activities that are often associated with mammalian glycosaminoglycans such as anti-inflammatory, antiosteoperotic, and anti-asthmatic. Glycosaminoglycans are complex linear polysaccharides ubiquitous in mammals that possess a wide range of biological activities. However, their presence and possible structural characteristics within O.ran. were previously unknown. In this study, glycosaminoglycans were isolated from O.ran. and their disaccharide compositions were analyzed by liquid chromatography-ion trap/time-of-flight mass spectrometry (LC-MS-ITTOF). Heparan sulfate (HS)/heparin (HP), chondroitin sulfate (CS)/dermatan sulfate (DS) and hyaluronic acid (HA) were detected in O.ran. with varied disaccharide compositions. HS species contain highly acetylated disaccharides, and have various structures in their constituent chains. CS/DS chains also possess a heterogeneous structure with different sulfation patterns and densities. This novel structural information could help clarify the possible involvement of these polysaccharides in the biological activities of O.ran. .